Consequences of screening English blood donors for HHV‐8 antibodies. Is it worth it?. (28th December 2015) - Tettmar, K. I.; Tuke, P. W.; Webster, M.; Lattimore, S.; Kitchen, A. D.; Schulz, T. F.; Tedder, R. S.
Abstract : Background: Human herpesvirus 8 (HHV‐8) is the causative agent of Kaposi's sarcoma which is of concern in organ transplantation due to transmission through either the donor organ or any associated blood components to immunologically susceptible patients. The prevalence of HHV‐8 in the UK has not been widely investigated. In this study, the seroprevalence of HHV‐8 in English blood donors was measured and the performance of confirmatory assays evaluated. Materials and Methods: Donation samples from 5009 English blood donors were screened for antibodies to HHV‐8. A combination of four different serological and molecular assays was used to investigate any IgG reactivity identified. Results: HHV‐8 repeatable serological reactivity in English blood donors was 0·7% but could not be confirmed as specific due to a lack of concordance in the confirmatory assays. Conclusions: These results suggest that the seroprevalence of HHV‐8 is extremely low amongst English donors. These data confirm findings from other studies which suggest a poor predictiveness of HHV‐8 serological assays, especially when used to screen asymptomatic populations. Where a change in donor demography can be anticipated in the UK, further seroprevalence studies should be considered, but only after careful evaluation and selection of the screening and confirmatory assays used.